Pengaruh Kualitas Pelayanan Front Liner terhadap Kepuasan Nasabah Perbankan Syariah di Bank Muamalat Cabang Palangka Raya - Farid Zaky Yopiannor; Nur Yasin (Pencerah Publik, 2016)
Front Liner body to customer satisfaction Bank Muamalat branch Palangka Raya. The methods used in this research are quantitative methods, data collection techniques using Angket (questionnaire), the number of samples in this research is as many as 345 customers of Bank Muamalat in Palangka Raya. Sampling techniques are by means of random sampling techniques or randomized samples, the analytical techniques used to process the data are with techniques of simple linear regression analysis. Results of analysis using simple linear regression in the equation can be regression (Y = a + BX), changed known Y = 26,885 + 0205 x, then there is the influence of Bak quality to the satisfaction of Bank Muamalat customers in the city of Palangka Raya